MEMBANGUN EARLY WARNING INDICATORS PERGERAKAN KURS DI INDONESIA: PENGEMBANGAN BUSINESS CYCLE ANALYSIS - Andra Devi Benazir; Noer Azam Achsani (Jurnal Manajemen & Agribisnis, 2008)
The economic crisis in 1997/1998 that was signed by depreciation rupiah almost destroyed the pillars of the economy. This exchange rate shock possibly will happen in the future like that happened in August 2007. At the same time, rupiah falled to the lowest level Rp. 9.410 per dollar (the exchange rate use the last month) in August 2007. The exchange rate of its daily until above Rp 9.500 per dollar (Sadewa, 2007). Therefore, it was needed indicator of theearly detection with build leading indicators the movement of the exchange rate in Indonesia. The purpose of this research is building leading indicators the movement of the exchangerate in Indonesia. It could give the capacity forecasting of the Indonesian economy of the movement direction in a manner the aggregate with the Business Cycle Analysis method andIts development. Empirical results showed that is received by four leading indicators and four coincident indicators. The real export, the real import, foreign currency deposit, and forexbanks demand deposits in foreign currency became the moving indicator preceded the exchange rate. Whereas, there are four indicators to coincident was foreign assets, interbank call money rate 1 day, the German share index (DAX), and the USA share index (Nasdaq). This condition indicated that the exchange rate rupiah really was affected by the external factor.